Archaeology of Louisiana - Rees, Mark A. (Book collections on Project MUSE., 2010)
Archaeology of Louisiana provides a groundbreaking and up-to-date overview of archaeology in the Bayou State, providing a thorough analysis of the cultures, communities, and people of Louisiana from the Native Americans of 13,000 years ago to the modern historical archaeology of New Orleans. With 18 chapters and 27 distinguished contributors, Archaeology of Louisiana brings together the work of some of the most respected archaeologists currently working in the state, collecting in a single volume a range of methods and theories to provide a comprehensive understanding of the latest archaeologi.